Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin

Beneficial effects of Stevioside on AGEs, blood glucose, lipid profile and renal status in streptozotocin-induced diabetic rats - Aswar, Urmila; Gogawale, Vinayak; Miniyar, Pankaj; Patil, Yugendra (Journal of Applied Biomedicine, 2019)
The advanced glycated end products (AGEs) are formed in the diabetic patients; it is a major cause of macrovascular and microvascular complications in diabetes. Clinically there is no treatment available for the AGEs. Stveoside (Stv), a sweetener has potent anti-diabetic and anti-oxidant activity. Hence, we investigated its use in prevention of AGEs formation using in vitro and in vivo models. Diabetes was induced by streptozotocin (STZ). These rats were kept without treatment till blood HbA1c was markedly increased. They were then divided into 5 groups and treated orally with vehicle or Metformin (MET) or Stv respectively for 28 days. Every 7th day, animals were tested for body weight and blood glucose (BG). On the last day of treatment, all the groups were evaluated for physiological and biochemical parameters, histopathology and AGEs; N-carboxymethyl-lysine (CML) estimation. Stv showed inhibition of AGEs in in vitro as well as in in vivo respectively. Positive effects were seen on the BG, lipid profile and urine parameters as well it showed reduced formation of CML. It also showed antihyperglycaemic, antihyperlipedemic and nephroprotective activities. The present study provides scientific rationale for the use of Stv as a sweetener with additional benefits in diabetes.
Keywords: AGEs; Diabetes; Diabetes complications; N-carboxymethyl-lysine; Stevioside; Streptozotocin

Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus